2014
DOI: 10.1111/wre.12124
|View full text |Cite
|
Sign up to set email alerts
|

Can the parasitic weeds Striga asiatica and Rhamphicarpa fistulosa co‐occur in rain‐fed rice?

Abstract: Striga asiatica and Rhamphicarpa fistulosa are important parasitic weeds of rain-fed rice, partly distributed in similar regions in sub-Saharan Africa (SSA). It is not evident whether their ecologies are mutually exclusive or partially overlapping. In Kyela, a rice-growing area in south Tanzania where both parasites are present, three transects of about 3 km each across the uplandlowland continuum were surveyed in June 2012 and 2013. A total of 36 fields were categorised according to their position on the upla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…They demonstrated that the adoption of control or prevention strategies for parasitic weeds is strongly correlated with farmers' access to credit, information and training; the same constraints that were prioritised by stakeholders in this study. Additionally, there is broad-based evidence showing that parasitic weed problems are a direct consequence of poor soil fertility (Kabiri et al, 2015;Parker, 2009), which directly relates to constraints such as untimely access to high quality inputs identified in this study. Following Klerkx et al (2012), addressing such generic constraints is likely to have a spillover effect on dealing with complex agricultural problems other than parasitic weeds.…”
Section: Institutional and Political Constraints And Opportunities Inmentioning
confidence: 96%
See 1 more Smart Citation
“…They demonstrated that the adoption of control or prevention strategies for parasitic weeds is strongly correlated with farmers' access to credit, information and training; the same constraints that were prioritised by stakeholders in this study. Additionally, there is broad-based evidence showing that parasitic weed problems are a direct consequence of poor soil fertility (Kabiri et al, 2015;Parker, 2009), which directly relates to constraints such as untimely access to high quality inputs identified in this study. Following Klerkx et al (2012), addressing such generic constraints is likely to have a spillover effect on dealing with complex agricultural problems other than parasitic weeds.…”
Section: Institutional and Political Constraints And Opportunities Inmentioning
confidence: 96%
“…Land tenure agreements, for instance, were not explicitly singled-out as a constraint while they form an institutional dimension related to parasitic weed problems. Parasitic weeds are particularly problematic on land characterised by poor soil fertility and water management (Kabiri et al, 2015). Such marginal land is often allocated to socio-economically disadvantaged groups such as women.…”
Section: Institutional and Political Constraints And Opportunities Inmentioning
confidence: 99%
“…Combined with knowledge on the environmental preferences of each weed, obtained from project 1 (e.g. Kabiri et al 2015), and figures obtained on their appearance, frequency, infestation rates, yield losses and the socio-economic factors affecting these variables obtained from project 3 (e.g. N'cho 2014), we can estimate a stochastic impact of parasitic weeds on rice production, using a diverse set of modeling techniques.…”
Section: Evaluating the Institutional Dimension Of Parasitic Weeds Anmentioning
confidence: 99%
“…The likelihood of infestation by R. fistulosa is higher on poorly fertile soils and fields located in the valley bottom and it is reduced through management practices such as late sowing and the application of medium-rate fertilizer (N'cho, Mourits, . Based on pot experiments combined with field measurements and observations, Kabiri et al (2015) concluded that the valley bottoms are the preferred habitat for R. fistulosa and that the soils in these valley bottoms can be characterized as poor in terms of fertility. An earlier study based on pot experiments, by Rodenburg et al (2011), showed that R. fistulosa can indeed be reduced by the application of inorganic fertilizers leading to increased (chemical) soil fertility.…”
Section: Evaluating the Institutional Dimension Of Parasitic Weeds Anmentioning
confidence: 99%
“…Ceci se rapportant essentiellement sur l'écologie. D'autres informations sur la biologie ont été données aussi par Ouédraogo et al (1999), Jones et al 1994, Kabiri et al (2015. La capacité de production de graines des phanérogames parasite est énorme.…”
Section: Introductionunclassified